Dictyostelium as a model to assess site-specific ADP-ribosylation events - Kolb, A-L; Hsu, D-W; Wallis, ABA; Ura, S; Rakhimova, A; Pears, CJ; Lakin, ND (Springer Verlag, 2018)
The amoeba Dictyostelium discoideum is a single-cell organism that can undergo a simple developmental program, making it an excellent model to study the molecular mechanisms of cell motility, signal transduction, and cell-type differentiation. A variety of human genes that are absent or show limited conservation in other invertebrate models have been identified in this organism. This includes ADP-ribosyltransferases, also known as poly-ADP-ribose polymerases (PARPs), a family of proteins that catalyze the addition of single or poly-ADP-ribose moieties onto target proteins. The genetic tractability of Dictyostelium and its relatively simple genome structure makes it possible to disrupt PARP gene combinations, in addition to specific ADP-ribosylation sites at endogenous loci. Together, this makes Dictyostelium an attractive model to assess how ADP-ribosylation regulates a variety of cellular processes including DNA repair, transcription, and cell-type specification. Here we describe a range of techniques to study ADP-ribosylation in Dictyostelium, including analysis of ADP-ribosylation events in vitro and in vivo, in addition to approaches to assess the functional roles of this modification in vivo.